2023
DOI: 10.1002/aenm.202300930
|View full text |Cite
|
Sign up to set email alerts
|

Spotting Interface Structuring during Na‐Insertion into the NaSICON Na3V2(PO4)3 by EQCM and Operando Fiber Optic Infrared Spectroscopy

Abstract: Reliable operation of Na-ion batteries requires a mastering of the interfacial processes governing intercalation kinetics. Ion desolvation, amongst others, is a crucial phenomenon as far as power applications are envisioned. Studying the intricacies of interfacial processes faces experimental challenges. Here the complementary use of electrochemical quartz crystal microbalance (EQCM) and operando infrared fiber evanescent wave spectroscopy (IR-FEWS) combined with molecular dynamics (MD) simulations is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…When comparing different materials, the firmness of solvent packing at a carbonate-based solvent at the electrode surface is greater at the NVP than at the NVPF, which actually explains the difference in the energy barriers: highly oriented solvent molecules at the interface require a higher energy contribution to change their configuration to solvate the diffusing Na + ion. In our recent EQCM study of the same systems under electrochemical cycling, we observed a detectable mass loss right before the insertion of Na + ions related to the desolvation only at the NVP, while in the case of NVPF, due to lose packing, the desolvation process remains confined within the penetration depth of the resonator’s acoustic wave and thus cannot be detected as a mass loss. When the carbonate series is compared, the difference in PMFs is not pronounced, but salt aggregation varies as a function of a solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing different materials, the firmness of solvent packing at a carbonate-based solvent at the electrode surface is greater at the NVP than at the NVPF, which actually explains the difference in the energy barriers: highly oriented solvent molecules at the interface require a higher energy contribution to change their configuration to solvate the diffusing Na + ion. In our recent EQCM study of the same systems under electrochemical cycling, we observed a detectable mass loss right before the insertion of Na + ions related to the desolvation only at the NVP, while in the case of NVPF, due to lose packing, the desolvation process remains confined within the penetration depth of the resonator’s acoustic wave and thus cannot be detected as a mass loss. When the carbonate series is compared, the difference in PMFs is not pronounced, but salt aggregation varies as a function of a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, we combined electrochemical quartz crystal microbalance and operando infrared fiber evanescent wave spectroscopy with MD to study the operation of Na-insertion material-based SIBs . We showed that upon insertion, a depletion of desolvated Na + occurs at the interface, which can impact the rate capability of the batteries and may be generic to other types of solvent/ionic species .…”
Section: Introductionmentioning
confidence: 99%
“…The ideal SSE should have excellent stability to ensure the safety of the battery, and should also have high ionic conductivity and low electronic conductivity to ensure high rate and cycling performance. At present, the commonly used materials of SSEs include garnets, [148] NASICON, [149,150] LISICON, [151] and sulfides, [152] and AI techniques have also been applied in the exploration of these SSE materials. [153] Wang et al proposed a target-driven ensemble learning framework for rapid screening and prediction of high-performance garnet type SSEs (Figure 11).…”
Section: Ai For Battery Materialsmentioning
confidence: 99%
“…Energy storage systems are of great significance to provide continuous and stable electricity supply from renewable energy in people’s daily life. Of the various electric energy storage systems, sodium-ion batteries (SIBs) have garnered considerable attention due to their abundant resources and low budget, making them one of the preferred choices for large-scale energy storage. Cathode materials including transition metal oxide, , polyanionic compounds, , organic materials, , and Prussian blue analogues (PBAs) play a crucial role in determining the battery performance. The spacious three-dimensional framework, substantial capacity, facile synthesis procedure, and high cost-effectiveness of PBAs make them attract tremendous interest.…”
Section: Introductionmentioning
confidence: 99%